Optimum Investment Strategy in the Power Industry Mathematical Models - Bartnik, Ryszard; Bartnik, Berenika; Hnydiuk-Stefan, Anna (SpringerBriefs in Applied Sciences and Technology, 2016)
This book presents an innovative methodology for identifying optimum investment strategies in the power industry. To do so, it examines results including, among others, the impact of oxy-fuel technology on CO2 emissions prices, and the specific cost of electricity production. The technical and economic analysis presented here extend the available knowledge in the field of investment optimization in energy engineering, while also enabling investors to make decisions involving its application. Individual chapters explore the potential impacts of different factors like environmental charges on costs connected with investments in the power sector, as well as discussing the available technologies for heat and power generation. The book offers a valuable resource for researchers, market analysts, decision makers, power engineers and students alike.